The Effect Music Therapy on Quality of Sleep - Fidya Anisa Firdaus; Reffi Nantia Khaerunnisa; Heri Ariyanto (Inspirasi Foundation, 2020)
Background Music therapy is a non-pharmacological therapy that combines mind-body therapy as an intervention technique that shapes thinking processes so that it affects psychological and physical conditions (bodily functions). Objectives This study aims to evaluate the efficacy of music on sleep quality accompanied by sleep complaints with or without comorbid medical conditions. Data Sources We conducted data searches from Cochrane, PubMed, Willey Online Library, JSTOR, Sage Journal, Taylor Francis Online, Springer and Science Direct. Method This study uses the PIOS (Participants, interventions, outcomes, Study design) and Mesh methods in finding data. Results Fourteen randomized controlled trials with six treatment conditions and a total of 633 participants with 319 participants in the intervention group and 314 controls met our inclusion criteria. Music therapy has a moderate effect on sleep quality of patients with sleep complaints with an average difference of -0.44 (95% CI: -1.01 to 0.33). Conclusion Music therapy is an initiative that is easy to implement, practical, and inexpensive and has no side effects and can be done in nursing practice to treat sleep problems in various populations in Indonesia.